Structure of basic emotions as a factor of emotional intelligence of high school students - Yulia A. Mochalova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The importance and predetermination of the emotional intelligence development as factors stimulating personal and professional growth of the individual and influencing his success in life are also undeniable. Emotional reaction is recognized as a specific type of knowledge that can enable a person to solve environmental problems successfully and correlate with the category of intelligence. Emotions and intellect are able to unite in their practical orientation. This combination is required for the coordinated development of the personality. The aim of the research was to study the role of such parameters of the basic emotions structure as the total functional resource of basic emotions; hierarchy of basic emotions; the balance of basic emotions in their totality in the level of emotional intelligence (EI) of high school students. The paper presents the results of an empirical study of the structure of basic emotions as a factor of emotional intelligence of high school students. Based on the results of the study, it was found that the parameter total functional resource of basic emotions decreases when moving to a sample of high school students with a higher IE, which may reflect a measure of chaos-orderliness in the structure of EI - a high value of this parameter reflects high chaos, and a low value - excessive ordering, which reduces the regulatory potential of EI. The parameter hierarchy of basic emotions has both general and specific features for high school students with different levels of EI. As for general features, they are: a) the emotion Interest which is the most distinguished; the second one is the Joy emotion. Specific features show that the Surprise emotion not only takes the third place in the hierarchy among high school students with high EI, but also reveals a significant increase in its share in the range of emotions. The parameter balance of basic emotions in their complex of high school students with different levels of EI can be quantitatively described by the parameters of the canonical hyperbolic rank parametric distribution, and the parameters of this distribution can be indicators of the level of high school students EI.